2015
DOI: 10.1021/acs.organomet.5b00419
|View full text |Cite
|
Sign up to set email alerts
|

N–H Activation of Ammonia by [{M(μ-OMe)(cod)}2] (M = Ir, Rh) Complexes: A DFT Study

Abstract: In this work, a computational study at the DFT level is carried out to determine the reaction mechanism for the N−H bond activation of ammonia by dinuclear [{M(μ-OMe)(cod)} 2 ] complexes (M = Ir, Rh) to yield amido species [{M(μ-NH 2 )(cod)} 2 ] reported experimentally by Mena et al. (Angew. Chem., Int. Ed. 2011, 50, 11735−11738). A stepwise mechanism is proposed for the replacement of μ-OMe bridging ligands considering associative or dissociative approaches for NH 3 coordination to the metal. Reaction pathwa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 81 publications
0
12
0
Order By: Relevance
“…The coordination of the quinoline nitrogen in the aromatic amide 1 to give a Rh( i )X species, followed by the oxidative addition of an N–H bond, gives complex A . 15 The insertion of 5a into the H–Rh bond in A gives complex B , which, after the elimination of HX, affords the carbene complex C . 16 The migratory insertion of the ortho C–H bond to a carbene moiety in the complex C through the oxidative addition of the ortho C–H bond followed by α-hydride migration gives D , 17 , 18 which undergoes reductive elimination followed by protonation to give the final product with regeneration of the Rh( i ) species.…”
Section: Resultsmentioning
confidence: 99%
“…The coordination of the quinoline nitrogen in the aromatic amide 1 to give a Rh( i )X species, followed by the oxidative addition of an N–H bond, gives complex A . 15 The insertion of 5a into the H–Rh bond in A gives complex B , which, after the elimination of HX, affords the carbene complex C . 16 The migratory insertion of the ortho C–H bond to a carbene moiety in the complex C through the oxidative addition of the ortho C–H bond followed by α-hydride migration gives D , 17 , 18 which undergoes reductive elimination followed by protonation to give the final product with regeneration of the Rh( i ) species.…”
Section: Resultsmentioning
confidence: 99%
“…Theoretical studies on transition metal complexes have also rationalized experimental data using trends in bond energies, formation of stable intermediates, and analysis of orbital interactions . Recently, it has been shown that diiridium organometallic complexes may cleave heterolytically the N–H bond assisted by metal–metal bonding interactions . Reaction pathways for hydroamination of olefins catalyzed by transition metal complexes have been determined by Poli and Leitner .…”
Section: Introductionmentioning
confidence: 99%
“…23 Recently, it has been shown that diiridium organometallic complexes may cleave heterolytically the N−H bond assisted by metal−metal bonding interactions. 24 Reaction pathways for hydroamination of olefins catalyzed by transition metal complexes have been determined by Poli 25 and Leitner. 26 Also, mechanistic details of the metal-free N−H bond activation of ammonia have been unraveled by Radosevich, 3a pointing out the participation of other ammonia molecules, resulting in an entropy-controlled electrophilic mechanism.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The oxidative addition of an N–H bond to a Rh center provides Rh( iii ) or Rh( iv ) 9 species A (see ESI for details † ) (the evidence of Rh( iv ) formation was that the solution turned to a dark purple colour). 10 In the next step, the insertion of an alkene into the Rh–H bond gives intermediate B , in which the NH hydrogen is transferred to the β position, as evidenced by deuterium labelling experiments ( Scheme 3a ). Two possible pathways are proposed from intermediate B .…”
Section: Resultsmentioning
confidence: 99%